2020
DOI: 10.1109/access.2020.2995552
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Connected Vehicle Dynamic Freeway Variable Speed Controller

Abstract: Traffic congestion is a major challenge in urban areas, and is associated with longer travel times, increased vehicle emissions, and numerous vehicle crashes. Creating an efficient mobility system is difficult, given that each driver is usually trying to optimize their individual trip within the network without accounting for other road users. However, new technologies in modern vehicles, especially connected vehicle technologies, make it increasingly possible to find solutions to network efficiency problems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The results showed that average travel time was reduced by 12%, total delay was reduced by 21%, and CO2 emissions were reduced by 3.3%. In addition, the authors' results showed that freeways benefit from the controller more than arterials [10].…”
Section: A Network Applicationsmentioning
confidence: 95%
“…The results showed that average travel time was reduced by 12%, total delay was reduced by 21%, and CO2 emissions were reduced by 3.3%. In addition, the authors' results showed that freeways benefit from the controller more than arterials [10].…”
Section: A Network Applicationsmentioning
confidence: 95%
“…This SPD-HARM controller, based on a sliding mode controller, was applied only to freeway sections. Abdelghaffar et al designed an SPD-HARM controller that regulates vehicle speeds in a speed harmonization zone to maintain downstream link vehicle speeds at the speed of capacity ( 4 , 54 ). The SPD-HARM controller is dynamic, does not require prior knowledge of bottleneck locations, and delivers recommended speeds to the vehicles on the network.…”
Section: Simulation Model Developmentmentioning
confidence: 99%
“…The objective is to keep the speed of link l , which is congested or about to be congested, v l , close to its speed at capacity v l true¯ . A detailed description of the SPD-HARM appears in Abdelghaffar et al ( 4 , 54 ).…”
Section: Simulation Model Developmentmentioning
confidence: 99%
“…In a more recent study, Abdelghaffar et al. have proposed a dynamic freeway speed controller to overcome vehicle emissions and crashes by decreasing the number of stops caused by traffic congestion [57]. They have presented the method based on sliding theory and CV environment.…”
Section: Analysis Of Vehicle Speed Assistance Approaches In Itsmentioning
confidence: 99%